The Effect of Gender Sensitivity Education on Sexuality Knowledge and Attitudes at Occupants of LPKA Kelas II B Sungai Raya Pontianak - Reni Novia; M Taufik; Otik Widyastutik (Jurnal Kesehatan Komunitas, 2019)
The Special Guidance Agency for Children (LPKA) has the task of fostering correctional students during their criminal period. The high cases of decency crimes in LPKA Kelas II B Sungai Raya Pontianak indicate a lack of adolescent knowledge and attitudes about sexuality. The purpose of this study was to determine the effect of gender sensitivity education on knowledge and attitudes about sexuality in occupants of LPKA Kelas II B Sungai Raya Pontianak. This research is a quantitative research with pre-experimental design with a one group pretest-posttest design approach. The number of samples is 17 respondents. The sampling technique is total sampling. Data were obtained using a questionnaire and analyzed by Wilcoxon test. The results showed that there was an increase in knowledge and attitudes about sexuality in occupants of LPKA Kelas II B Sungai Raya Pontianak after being given gender sensitivity education. There were significant differences in knowledge (0.001 < 0.05) and attitudes (0.010 < 0.05) before and after being given gender sensitivity education about sexuality in occupants of LPKA Kelas II B Sungai Raya Pontianak. Thus, gender sensitivity education can be used as a means of effective health education in changing knowledge and attitudes.